DOP84 Risankizumab maintenance therapy results in sustained improvements in endoscopic outcomes in patients with moderate to severe Crohn's Disease: Post-hoc analysis from the phase 3 study FORTIFY. (21st January 2022) - Irving, P M; Abreu, M; Axler, J; Gao, X; Torres, J; Neimark, E; Song, A; Wallace, K; Kligys, K; Berg, S; Liao, X; Panaccione, R
Abstract: Background: Data from Phase 3 studies in Crohn's disease (CD) demonstrated significant improvements in endoscopic outcomes with risankizumab (RZB) versus placebo (PBO) following 12-weeks (wks) induction therapy. Continued maintenance therapy with 360mg RZB SC led to significantly higher rates of endoscopic response and remission at Wk52 compared to withdrawal/placebo. This post-hoc analysis examined the durability of SC RZB maintenance therapy for endoscopic outcomes among patients achieving these endpoints at the end of induction Methods: Patients achieving clinical response with 12-wks IV RZB induction therapy in ADVANCE or MOTIVATE entered the maintenance study, FORTIFY, and received either RZB SC or had RZB withdrawn and received placebo for 52 wks. For this analysis, endoscopic outcomes in the RZB 360 mg SC (N=141) and withdrawal/placebo (N=164) arms are reported. Maintenance of endoscopic response, endoscopic remission, and/or an SES-CD score of 0–2 were assessed at Wk52 in patients who achieved these endpoints at Wk0 of maintenance (Wk12 of induction). Safety was assessed throughout the study. Results: Following 12-wks of IV RZB induction therapy (FORTIFY Wk0), 141 patients were randomized to RZB 360 mg (patients achieving endoscopic response, 55/141; endoscopic remission, 39/141; SES-CD score of 0–2, 29/141) and 164 were randomized to withdrawal (PBO SC) (patients achieving endoscopic response, 73/164; endoscopic remission, 46/164; SES-CD 0–2, 32/164). Maintenance of endoscopic response at Wk52 was demonstrated in 70.2% (39/55) of patients receiving RZB 360 mg SC versus 38.4% (28/73) of patients in the withdrawal (PBO SC) arm ( P <0.001). Maintenance of endoscopic remission at Wk52 was demonstrated in 74.4% (29/39) of patients receiving RZB 360 mg versus 23.9% (11/46) of patients in the withdrawal (PBO SC) arm ( P <0.001). Maintenance of an SES-CD score from 0–2 at Wk52 was demonstrated in 65.5% (19/29) of patients receiving RZB 360 mg versus 21.9% (7/32) of patients in the withdrawal (PBO SC) arm ( P <0.001).RZB maintenance treatment was well-tolerated and no new safety signals were observed. The safety profile of RZB has been reported previously. 1–5 Conclusion: RZB IV induction followed by SC maintenance therapy led to sustained improvements in endoscopic outcomes, demonstrating the durability of efficacy with continued RZB treatment in patients with moderate to severe CD. Reference: 1. Feagan, B. G. et al. Lancet 389, 1699–1709 (2017) 2 Feagan, B. G. et al. Lancet Gastroenterol Hepatol 3, 671–680 (2018) 3 Ferrante, M. et al. Journal of Crohn's and Colitis jjab093 (2021) 4 Ferrante, M. et al. in UEGW 2021 5 D'Haens, G. et al. in DDW 2021